Long-term temporal variations and source changes of halocarbons in the Greater Pearl River Delta region, China. (1st August 2020) - Zeng, Lewei; Dang, Juan; Guo, Hai; Lyu, Xiaopu; Simpson, Isobel J.; Meinardi, Simone; Wang, Yu; Zhang, Luyao; Blake, Donald R.
Abstract: Halocarbons are widely used in the Greater Pearl River Delta (PRD) region of China. To study the long-term trends, source changes and emissions of major halocarbons, a total of 1505 canister air samples were collected in the Greater PRD region during 2001–2018. Mixing ratios of CFCs decreased significantly over the past 18 years except for CFC-114, which significantly increased in the Greater PRD, consistent with the recent observations of significant CFC-114 emissions in East Asia. Declines in CFCs in the Greater PRD region were faster than those at the background Mauna Loa (MLO) site, indicating effective control regulations. Source apportionment simulations showed that refrigeration applications, including refrigeration industry and CFCs replacement, were the main sources of halocarbons. During the study period, refrigeration industry experienced a progressive decline in both mixing ratio and percentage, while the contribution of CFCs replacement remained increasing. Contribution of solvent use in electronic industry traced by C2 Cl4 dramatically decreased during the study period, and stayed at a low level in recent years. Based on the measured ratios of halocarbons to CO, the estimated total halocarbon emissions in 2016 were 46.5 ± 16.7 Gg for the Greater PRD region. This study provides useful information for examining the evolving emission status of halocarbons in the Greater PRD region in response to control strategies and changing usage. Highlights: Mixing ratios of CFCs decreased over the past 18 years except for CFC-114, which increased in the Greater PRD region. Refrigeration applications were the main sources of halocarbons in the Greater PRD region. Refrigeration industry dominated by CFCs decreased during the past 18 years, while source of CFCs replacement increased. The estimated total halocarbon emissions in 2016 were 46.5 ± 16.7 Gg for the whole Greater PRD region.